The Harvard Business Review Leader's Handbook - Ashkenas, Ron; Manville, Brook (Ascent Audio, 2020)
Put aside all the overhyped new frameworks, the listicles, the "10 best things you need to succeed as a leader today." The critical leadership practices-the ones that will allow a leader to make the biggest impact over time-are well established. They're about how you create a vision and inspire others to follow it. How you make difficult strategic choices. How you lead innovation. How you get results. In this comprehensive handbook, strategy and change experts Ron Ashkenas and Brook Manville distill proven ideas and frameworks about leadership from Harvard Business Review, interviews with senior executives, and their own experience in the field-all to help rising leaders stand out and have a big impact. In The HBR Leader's Handbook you'll find: concise explanations of proven leadership frameworks from Harvard Business Review contributors such as Clayton M. Christensen and Michael E. Porter; in-depth case studies of senior leaders such as Jim Wolfensohn at the World Bank, Paula Kerger at PBS, Darren Walker at the Ford Foundation, and Jim Smith at Thomson Reuters; and step-by-step guidance to help you understand and start implementing six core leadership practices: building a unifying vision, developing a strategy, getting great people on board, focusing on results, innovating for the future, and leading yourself.